Predicting health‐related quality of life 2 years after moderate‐to‐severe traumatic brain injury. (29th April 2013) - Forslund, M. V.; Roe, C.; Sigurdardottir, S.; Andelic, N.
Abstract : Aims: To describe health‐related quality of life (HRQL) 2 years after moderate‐to‐severe traumatic brain injury (TBI) and to assess predictors of HRQL. Materials and methods: A prospective cohort study of 91 patients, aged 16–55 years, admitted with moderate‐to‐severe TBI to a trauma referral centre between 2005 and 2007, with follow‐up at 1 and 2 years. Mean age was 31.1 (SD = 11.3) years, and 77% were men. Injury severity was evaluated by the Glasgow Coma Scale (GCS), head CT scan (using a modified Marshall Classification), Injury Severity Score (ISS) and post‐traumatic amnesia (PTA). The Functional Independence Measure (FIM), Community Integration Questionnaire (CIQ), Beck Depression Inventory (BDI) and Medical Outcomes 36‐item Short Form Health Survey (SF‐36) were administered at follow‐up visits. The main outcome measures were the Physical Component Summary (PCS) and Mental Component Summary (MCS) of the SF‐36. Results: HRQL appears to be relatively stable between 1 and 2 years after injury. In the multivariate linear regression, younger age ( β  = −0.20, P  = 0.032), more severe TBI ( β  = 0.28, P  = 0.016), more severe overall trauma ( β  = 0.22, P  = 0.026), higher levels of community integration ( β  = 0.36, P  = 0.019) and higher positive change in PCS scores from 1 to 2 years ( β  = 0.41, P  < 0.001) predicted better self‐reported physical health 2 years post‐TBI. Lower scores for depression ( β  = −0.70, P  < 0.001) and a higher positive change in MCS scores ( β  = 0.62, P  < 0.001) predicted better self‐reported mental health. Conclusions: Future interventions should focus on aspects related to HRQL that are more easily modified, such as physical functioning, home and social integration, productivity, and mental and emotional status.